eyePay (2018)
"We have decided to design aid mechanisms that could help sightless individuals, recognize bills by using identification methods based on the visual aids which they currently aren?t able to use. Since most blind people can't recognize bills denomination and even less the authenticity of it, it is a problem and it should be addressed. Since most people who suffer this situation can't recognize how much a fare is worth or even less if its authentic or not, it is important for us to design and develop a personal device that not only describe the bills value but if its authentic or not."--Tomado del Formato de Documento de Grado